1991
DOI: 10.1017/s0033291700022388
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of life of the individual: the SEIQoL with a healthy and a gastroenterology unit population

Abstract: SYNOPSIS Current methods of measuring quality of life (QoL) impose an external value system on individuals, rather than allowing them to describe their lives in terms of those factors which they consider important. The Schedule for the Evaluation of Individual Quality of Life (SEIQoL) was developed to overcome such limitations. The QoL of 42 healthy attenders at an international immunization clinic was assessed using SEIQoL. Judgement reliability was high (r = 0-74) and individuals' judgement policies accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
1
9

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(191 citation statements)
references
References 28 publications
9
172
1
9
Order By: Relevance
“…The within-patient reliability found in this study was comparable to that found in other studies using JA in patients [10]. The range of scores for replicated judgments indicated that several patients found the task difficult.…”
Section: Perceptions Of Asthma Severity Ea Barley and Pw Jonessupporting
confidence: 88%
See 1 more Smart Citation
“…The within-patient reliability found in this study was comparable to that found in other studies using JA in patients [10]. The range of scores for replicated judgments indicated that several patients found the task difficult.…”
Section: Perceptions Of Asthma Severity Ea Barley and Pw Jonessupporting
confidence: 88%
“…JA has been used to determine judgment policies used by clinicians when making clinical decisions [6][7][8]. It has also been used in patients to measure individual quality of life [9][10][11]. Judgment policies derived using these methods have been shown to relate well to actual decision-making [12,13].…”
mentioning
confidence: 99%
“…In health related studies, it has been used in people suffering from peptic ulcer disease and irritable bowel disease (18), osteoarthritis (19), AIDS (20), cancer (21,22), cystic fibrosis (23), stroke (24), multiple sclerosis (17), mental illness (25), amyotrophic lateral sclerosis (26,27), people with leukaemia and lymphoma (28), people with End Stage Renal Failure (29), carers of people with dementia (30), and young people with diabetes (31) to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, disease-specific tools may be more appropriate than generic ones in clinical practice (70). The newer genre of patient-specific (individualized) quality-of-life measures (67,81,90,110) may prove most illuminating at the individual-patient level. It is clear from studies of mental health screening that the mere availability of screening tools constitutes neither a necessary nor sufficient condition for routine clinical use (3).…”
Section: Clinical Practicementioning
confidence: 99%
“…In addition to generic, disease-specific, and utility measures, tools have been developed to measure patient-specific (individualized) quality of life (67,81,90,110). Over 75 different tools exist that measure functional ability in the elderly and the chronically ill (23).…”
Section: Selection Of Measuresmentioning
confidence: 99%